Two-stage threshold representations - Paola Manzini; Christopher J. Tyson; Marco Mariotti (Theoretical Economics, 2013)
We study two-stage choice procedures in which the decision maker first preselects the alternatives whose values according to a criterion pass a menu-dependent threshold, and then maximizes a second criterion to narrow the selection further. This framework overlaps with several existing models that have various interpretations and impose various additional restrictions on behavior. We show that the general class of procedures is characterized by acyclicity of the revealed "first-stage separation relation."
Keywords: D01; D03; D70; 330; Attention; choice function; revealed preference; satisficing